The Recommended Time Interval of Decision to Incision in Caesarean Section is not Achieved in Daily Practice - Guntur, Novia (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objective: To determine the mean time for decision-to-incision interval for emergency caesarean section, the contributing factors for delay and the outcome at Department of Obstetrics and Gynecology Dr. Moh. Hoesin Hospital, Palembang. Methods: The study was conducted on 555 patients who met our study inclusion criteria at our maternity unit. There was 1748 deliveries in six months and the rate of caesarean section was approximately 37.9% (6.1% elective). An emergency caesarean section was defined as non-elective or non-scheduled cases. Result: In this study, there was 355 emergency caesarean sections, and the mean time from decision-to-incision was 83.9±41.6 minutes. The time interval reached 30 minutes in only 8 women (2.2%). Most cases have time interval 61-90 minutes (41.1%). The main sources of delay were patient’s preparations, transfer of women to the operating theatre, operating theatre preparations and the start of anesthesia administration. The most common indication for emergency caesarean sections were dystocia, bleeding from placenta previa or placental abruption, premature rupture of membrane and fetal distress. There were significant differences in the proportion of babies born with 1 minute Apgar score